2000
DOI: 10.1006/viro.2000.0589
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Hypodermal and Hematopoietic Necrosis Virus of Shrimp Is Related to Mosquito Brevidensoviruses

Abstract: We purified and sequenced infectious hypodermal and hematopoietic necrosis virus (IHHNV), a small DNA virus of shrimp, from wild Penaeus stylirostris. The virion has a buoyant density of 1.45 as determined by cesium chloride gradient. Analysis of 3873 nucleotides of the viral genome revealed three large open reading frames (ORFs) and parts of the noncoding termini of the viral genome. The left, mid, and right ORFs on the complementary (plus) strand have potential coding capacities of 666 amino acids (aa) (75.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
111
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 37 publications
0
111
0
1
Order By: Relevance
“…Dhar et al (2007) demonstrated transient expression of luciferase under the control of P2 promoter in the constructed vector P2 complete pGL3, even though the results were variable. Because, it is located near map unit 2, Shike et al (2000) named the promoter P2. In the present study, the same P2 promoter was used for constructing the recombinant baculovirus.…”
Section: Discussionmentioning
confidence: 99%
“…Dhar et al (2007) demonstrated transient expression of luciferase under the control of P2 promoter in the constructed vector P2 complete pGL3, even though the results were variable. Because, it is located near map unit 2, Shike et al (2000) named the promoter P2. In the present study, the same P2 promoter was used for constructing the recombinant baculovirus.…”
Section: Discussionmentioning
confidence: 99%
“…Based on physicochemical and ultrastructural properties of the virion and genomic organization, IHHNV is taxonomically placed under the Parvoviridae family [9,55,74]. These are small icosahedral, nonenveloped viral particles 20-22 nm in diameter containing a single-stranded, linear DNA of approximately 3.9 kb [44,69].…”
Section: Morphologymentioning
confidence: 99%
“…AF218266) and Mexico [74]. Nucleotide sequence analysis of the Indian IHHNV genome reveals three major coding domains: a left ORF (NS1) of 2,001 bp, a mid ORF (NS2) of 1,092 bp and a right ORF (VP) of 990 bp (Fig.…”
Section: Genome Organizationmentioning
confidence: 99%
See 2 more Smart Citations